Factors related to employment in childhood cancer survivors in Japan: A preliminary study - Kobayashi, Kyoko; Ishida, Yasushi; Gunji, Michiyo; Nagase, Kyoko; Yoshimoto-Suzuki, Yuri; Hosoya, Yosuke; Hasegawa, Daisuke; Manabe, Atsushi; Ohde, Sachiko; Ozawa, Miwa (Frontiers in Pediatrics, 2022)
Purpose Previous research has revealed vocational and academic difficulties in childhood cancer survivors, and explored impact of survivors' medical history and physical function on vocational and academic status. However, we often encounter survivors with similar diagnoses and late effects but different academic or employment statuses. This raises the question of what affects academic attainment and employment other than treatment or late effects. This study aimed to explore factors associated with childhood cancer survivors' employment status and academic achievement. Methods Comprehensive health check-up and questionnaire survey were conducted for 69 survivors who were over the age of 18 and participated in St. Luke's Lifetime cohort study. We obtained survivors' biological function using comprehensive health check-up, neurocognitive states, quality of life, transition readiness, and family function. We conducted univariate analysis (Mann–Whitney U tests or chi-square tests) to compare the differences between the regular workers/students and non-regular workers/unemployed groups. The variables with p-values <0.1 were used as independent variables multivariate logistic regression to explore predictors of employment status and academic attainment. Results Result of the univariate analysis, intelligence quotient, SF-8 PCS, transition readiness, family function were used for multivariate logistic regression as independent variables. The stepwise likelihood method was conducted; intelligence quotient (odds ratio [OR] = 1.100; 95% confidence interval [CI] 1.015–1.193; p = 0.021), transition readiness (OR = 0.612; 95% CI 0.396–0.974; p = 0.038), and family function (OR = 2.337; 95% CI 1.175–4.645; p = 0.015) were found to be associated with survivors' regular workers/students in the final regression model. Conclusion Long-term follow-up of pediatric cancer survivors requires the provision of total care, which supports physical, psychological, and social functions to improve health, readiness for transition to self-management, and family functioning.